Nitrosamines in rubber gloves used for food contact applications - Pinprayoon, Orawan; Bhumirabeab, Pantila; Onjun, Orasa (Bulletin of Applied Sciences, 2022)
Rubber gloves are used daily in various applications including for food handling purposes. In order to assess possible exposure of the wearers to N-nitrosamines as well as possible release of N-nitrosamines to foods being contacted to these gloves, effects of extraction media are investigated. Artificial saliva, artificial sweats, and some food simulants are used for the extractions and twelve N-nitrosamines including NDMA, NDEA, NDPA, NDiBA, NDBA, NPIP, NPYR, NMOR, NEPhA, NMPhA, NDiNA, and NDBzA are analysed using GC-TEA. By using different extraction media, the levels of the released N-nitrosamines and N-nitrosatable substances are different leading to the differences in the judgement for the EU Directive compliance. By comparing with data of daily intake of N-nitrosamines from foods, the intake of N-nitrosamines migrated from gloves used for food handling under the most unfavourable circumstances could lead to an exceeding of dietary intake. It is suggested that only rubber gloves certified for selected purpose should be used for food contact application.